Analysis of early puberty in girls leads to physical, psychological, and social consequences (KHD-Production, 2025)
Early puberty in girls before the age of 9 may lead to physical, psychological, and social consequences, including risks of obesity, menstrual disorders, risky sexual behavior, as well as early marriage and pregnancy. This study aimed to analyze early puberty in girls leading to physical, psychological, and social consequences in Tanah Baru village, Beji subdistrict, Depok, West Java. This mixed-method research applied an exploratory sequential approach. The sample consisted of 100 participants selected through a total sampling approach. Core informants included four respondents, while key informants comprised four parents/guardians and three class teachers, all recruited using snowball sampling. Research instruments included questionnaires and interview guides. The data were analyzed using univariate, bivariate (Chi-Square test), and multivariate (multiple logistic regression) analyses. Qualitative analysis revealed that girls experiencing early puberty expressed feelings of anxiety, confusion, and embarrassment due to faster physical changes compared to their peers. Parents reported difficulties in providing education, particularly in areas such as reproductive health and emotional regulation. Teachers noted challenges in guiding children who appeared physically mature but were still psychologically immature, particularly in social interactions at school. Quantitative analysis revealed that factors significantly associated with early puberty included maternal age at menarche (p = 0.029), nutritional status (p = 0.002), fast food consumption (p = 0.001), physical activity (p = 0.001), stress (p = 0.001), and exposure to pornography (p = 0.001). Multivariate analysis indicated that the most dominant factors influencing early puberty were physical activity, stress, and exposure to pornography. Prevention efforts for early puberty in girls should focus on promoting physical activity, encouraging healthy eating habits, managing stress, and monitoring media exposure.